High-strength and low-VOC thermoplastic resin composite material and preparation method thereof

By synthesizing high-strength, low VOC thermoplastic resin composite materials, and using diatomaceous earth, sodium carbonate and other materials to prepare VOC improved fillers and modified wollastonite, the problem of insufficient mechanical properties and VOC performance of existing thermoplastic resin composite materials has been solved, and performance improvement and application areas have been achieved.

CN119708689APending Publication Date: 2025-03-28HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311269968.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The lack of mechanical properties and VOC properties of existing thermoplastic resin composites in certain application fields limits their application range.

Method used

By synthesizing a high-strength, low VOC thermoplastic resin composite material, using diatomaceous earth, sodium carbonate, surfactant and 2-ethylacrylic acid and other materials, VOC improved filler and modified wollastonite are prepared, combined with thermoplastic resin, antioxidant and other components, and the composite material is prepared through the extrusion granulation process.

Benefits of technology

The mechanical properties and VOC properties of thermoplastic resin composites have been significantly improved, and their application potential in specific application fields has been expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-strength and low-VOC (volatile organic compound) thermoplastic resin composite material and a preparation method thereof. The high-strength and low-VOC thermoplastic resin composite material is prepared from the following components in parts by weight: 90-110 parts of thermoplastic resin, 8-12 parts of VOC improved filler, 6-10 parts of modified wollastonite and 0.1-0.5 part of an antioxidant. The invention provides a high-strength low-VOC thermoplastic resin composite material and a preparation method thereof, the high-strength low-VOC thermoplastic resin composite material has good VOC performance and mechanical property, and the technical problem that the mechanical property and VOC capacity of thermoplastic resin in the prior art are limited is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to a high-strength, low-VOC thermoplastic resin composite material and a preparation method thereof. Background Art

[0002] Compared with thermosetting resins, thermoplastic resins can be recycled and are widely used. Thermoplastic resins have advantages such as good fatigue resistance, good heat resistance, and excellent dimensional stability. However, in some specific application fields, the mechanical properties and VOC performance of thermoplastic resins are very high, which limits the application of thermoplastic resin composites in some specific fields.

[0003] In view of these deficiencies, the present invention innovatively synthesizes a thermoplastic resin composite material with good mechanical properties and VOC performance, and the thermoplastic resin composite material has good mechanical properties and VOC performance, which has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention

[0004] In view of this, the present invention provides a high-strength, low-VOC thermoplastic resin composite material and a preparation method thereof, which has excellent VOC performance and mechanical properties, and solves the technical problems of limited mechanical properties and VOC capacity of thermoplastic resins in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention discloses a high-strength, low-VOC thermoplastic resin composite material, which is composed of the following components in parts by weight:

[0007]

[0008] As a further solution of the present invention: the preparation method of the VOC improved filler comprises the following steps:

[0009] (1) Weigh diatomaceous earth, sodium carbonate, surfactant, and deionized water, add them to a reaction vessel, and stir and react at 40-60° C. for 16-20 h to obtain solution A;

[0010] (2) The solution A is filtered, washed, and vacuum dried to obtain a VOC improved filler.

[0011] As a further solution of the present invention: the mass ratio of diatomaceous earth, sodium carbonate and surfactant is (30-40): (10-16); (0.6-0.8): (160-240).

[0012] As a further embodiment of the present invention: the surfactant is octadecyl dimethyl ammonium bromide.

[0013] As a further solution of the present invention: the preparation method of the modified wollastonite comprises the following steps:

[0014] Put 2-ethylacrylic acid and wollastonite into a high-speed mixer, stir them thoroughly at 30-40°C, cool them to room temperature, and sieve them to obtain modified wollastonite.

[0015] As a further embodiment of the present invention: the antioxidant is at least one of Irganox168, Irganox1010 and Irganox1330.

[0016] As a further solution of the present invention: the thermoplastic resin is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate, and polyamide 6.

[0017] Another aspect of the present invention discloses a method for preparing the thermoplastic resin composite material as described in any one of the above, comprising the following steps:

[0018] (1) weighing a thermoplastic resin, a VOC-modified filler, a modified wollastonite, and an antioxidant according to parts by weight, mixing and stirring to obtain a mixed material;

[0019] (2) The mixed material is placed in an extruder for extrusion and granulation to obtain a thermoplastic resin composite material.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The cationic surfactant octadecyl dimethyl ammonium bromide modified the surface of diatomite, so that the sample surface had some cationic groups, which indeed improved its adsorption performance for small molecular volatile gases. Under the action of the surfactant dodecyl dimethyl ammonium bromide, the carbonate ions were doped to form a layered structure on the diatomite, which increased its specific surface area and formed a mesoporous structure, increasing the occurrence sites on its surface and inside, which was more conducive to the adsorption of small molecular volatile gases.

[0022] (2) 2-Ethyl acrylic acid has a double bond and a carboxyl group. When it is mixed with wollastonite, the carboxyl group can bind to the Ca 2+ Chemical reactions occur, and the surface of wollastonite is coated with a single molecule of a stable ionic structure. Since the other end of 2-ethyl acrylic acid has an unsaturated double bond, this modified filler has a strong reactivity. After being mixed with a thermoplastic resin, due to the mechanical shear force during the processing and molding process, the thermoplastic resin will produce free radicals that react with the unsaturated double bonds on the surface of wollastonite to form a stable chemical cross-linking structure, improve the compatibility between the thermoplastic resin and wollastonite, and improve the physical properties of the thermoplastic resin composite material.

[0023] (3) The present invention synthesizes a thermoplastic resin composite material with excellent VOC performance and physical properties, which has great promotion value. DETAILED DESCRIPTION

[0024] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0026] The raw material manufacturers and brand information used in the following preparation examples, embodiments and comparative examples are as follows:

[0027] Polybutylene terephthalate (PBT), grade 1200-211L, Changchun, Taiwan, China;

[0028] Polypropylene (PP), brand Z30S, Maoming Petrochemical;

[0029] Polyethylene (PE), brand 5070, Panjin Ethylene;

[0030] Polyamide 6 (PA6), brand IM, Russian Gubi;

[0031] Polystyrene (PS), brand 350, Guoqiao, Taiwan, China;

[0032] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;

[0033] Diatomaceous earth, Hebei Xinxu Mineral Products Co., Ltd.;

[0034] Sodium carbonate, Jinan Hongwen Chemical Co., Ltd.;

[0035] Octadecyl dimethyl ammonium bromide, Hunan Zhenyuan Chemical Co., Ltd.;

[0036] Ethyl acrylic acid, Guangdong Wengjiang Chemical Reagent Co., Ltd.;

[0037] Antioxidants Irganox168, Irganox1010, Irganox1330, BASF.

[0038] The test instruments used in the embodiments and comparative examples are as follows:

[0039] ZSK30 twin-screw extruder, W&P, Germany; JL-1000 tensile testing machine, Guangzhou Guangcai Experimental Instrument Co., Ltd.; HTL900-T-5B injection molding machine, Haitai Plastic Machinery Co., Ltd.; XCJ-500 impact testing machine, Chengde Testing Machine Factory; QT-1196 tensile tester, Dongguan Gaotai Testing Instrument Co., Ltd.; QD-GJS-B12K high-speed mixer, Beijing Hengaode Instrument Co., Ltd.

[0040] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0041] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0042] Preparation Example 1

[0043] (1) Weigh 300 g of diatomaceous earth, 100 g of sodium carbonate, 6 g of surfactant, and 1.6 kg of deionized water, add them to a reaction vessel, stir and react at 40° C. for 16 h to obtain solution A.

[0044] (2) Solution A was filtered, washed, and dried in a vacuum drying oven at 60° C. for 3 h to obtain VOC improved filler M1.

[0045] Preparation Example 2

[0046] (1) Weigh 60 g of 2-ethylacrylic acid and 300 g of wollastonite into a high-speed mixer and stir at 30° C. for 2 h to obtain a mixture.

[0047] (2) The mixture was cooled to room temperature and passed through an 800-mesh sieve to obtain modified wollastonite N1.

[0048] Example 1

[0049] (1) Weigh 90 parts of PP, 8 parts of VOC improved filler M1, 6 parts of modified wollastonite N1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0050] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.

[0051] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0052] Comparative Example 1

[0053] (1) Weigh 90 parts of PP, 6 parts of modified wollastonite N1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0054] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.

[0055] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0056] Comparative Example 1-1

[0057] (1) Weigh 90 parts of PP, 8 parts of VOC improved filler M1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0058] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1-1.

[0059] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0060] The PP composite materials prepared in the above Example 1, Comparative Example 1 and Comparative Example 1-1 were made into strips for testing using an injection molding machine. The test data are shown in Table 1 below:

[0061] Table 1

[0062]

[0063] It can be seen from the above table that, comprehensively speaking, the mechanical properties and VOC performance of Example 1 are better.

[0064] Preparation Example 3

[0065] (1) Weigh 400 g of diatomaceous earth, 160 g of sodium carbonate, 8 g of surfactant octadecyl dimethyl ammonium bromide, and 2.4 kg of deionized water, add them to a reaction vessel, stir and react at 60° C. for 20 h to obtain solution A.

[0066] (2) Solution A was filtered, washed, and dried in a vacuum drying oven at 80° C. for 5 h to obtain VOC-improved filler M2.

[0067] Preparation Example 4

[0068] (1) Weigh 100 g of 2-ethylacrylic acid and 400 g of wollastonite into a high-speed mixer and stir at 40° C. for 4 h to obtain a mixture.

[0069] (2) The mixture was cooled to room temperature and passed through an 800-mesh sieve to obtain modified wollastonite N2.

[0070] Example 2

[0071] (1) Weigh 110 parts of PBT, 12 parts of VOC improved filler M2, 10 parts of modified wollastonite N2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0072] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.

[0073] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0074] Comparative Example 2

[0075] (1) Weigh 110 parts of PBT, 10 parts of modified wollastonite N2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0076] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.

[0077] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0078] Comparative Example 2-1

[0079] (1) Weigh 110 parts of PBT, 12 parts of VOC improved filler M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0080] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2-1.

[0081] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0082] The PBT composite materials prepared in the above Example 2, Comparative Example 2 and Comparative Example 2-1 were made into strips by injection molding machine for testing. The test data are shown in Table 2:

[0083] Table 2

[0084]

[0085] It can be seen from the above table that, overall, the mechanical properties and VOC performance of Example 2 are better.

[0086] Preparation Example 5

[0087] (1) Weigh 350 g of diatomaceous earth, 130 g of sodium carbonate, 7 g of surfactant octadecyl dimethyl ammonium bromide, and 2.0 kg of deionized water, add them to a reaction vessel, stir at 50° C. for 18 h, and obtain solution A.

[0088] (2) Solution A was filtered, washed, and dried in a vacuum drying oven at 70° C. for 4 h to obtain VOC improved filler M3.

[0089] Preparation Example 6

[0090] (1) Weigh 80 g of 2-ethylacrylic acid and 350 g of wollastonite into a high-speed mixer and stir at 35° C. for 3 h to obtain a mixture.

[0091] (2) The mixture was cooled to room temperature and passed through an 800-mesh sieve to obtain modified wollastonite N3.

[0092] Example 3

[0093] (1) Weigh 100 parts of PE, 10 parts of VOC improved filler M3, 8 parts of modified wollastonite N3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;

[0094] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.

[0095] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0096] Comparative Example 3

[0097] (1) Weigh 100 parts of PE, 8 parts of modified wollastonite N3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;

[0098] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D3.

[0099] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0100] Comparative Example 3-1

[0101] (1) Weigh 100 parts of PE, 10 parts of VOC improved filler M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;

[0102] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D3-1.

[0103] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0104] The PE composite materials prepared in the above Example 3 and Comparative Example 3 were made into test strips by an injection molding machine. The test data are shown in Table 3 below:

[0105] Table 3

[0106]

[0107] It can be seen from the above table that, overall, the mechanical properties and VOC performance of Example 3 are better.

[0108] Preparation Example 7

[0109] (1) Weigh 338 g of diatomaceous earth, 155 g of sodium carbonate, 6.9 g of surfactant octadecyl dimethyl ammonium bromide, and 2.35 kg of deionized water, add them to a reaction vessel, stir and react at 48° C. for 19 h to obtain solution A.

[0110] (2) Solution A was filtered, washed, and dried in a vacuum drying oven at 78° C. for 5 h to obtain VOC improved filler M4.

[0111] Preparation Example 8

[0112] (1) Weigh 69 g of 2-ethylacrylic acid and 389 g of wollastonite into a high-speed mixer and stir at 38° C. for 4 h to obtain a mixture.

[0113] (2) The mixture was cooled to room temperature and passed through an 800-mesh sieve to obtain modified wollastonite N4.

[0114] Example 4

[0115] (1) Weigh 95 parts of PA6, 10.5 parts of VOC improved filler M4, 9.5 parts of modified wollastonite N4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0116] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.

[0117] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0118] Comparative Example 4

[0119] (1) Weigh 95 parts of PA6, 9.5 parts of modified wollastonite N4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0120] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D4.

[0121] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0122] Comparative Example 4-1

[0123] (1) Weigh 95 parts of PA6, 10.5 parts of VOC improved filler M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0124] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D4-1.

[0125] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0126] The PA6 composite materials prepared in the above Example 4, Comparative Example 4 and Comparative Example 4-1 were made into strips by injection molding machine for testing. The test data are shown in Table 4:

[0127] Table 4

[0128]

[0129] It can be seen from the above table that, comprehensively, the mechanical properties and VOC performance of Example 4 are better.

[0130] Preparation Example 9

[0131] (1) Weigh 346 g of diatomaceous earth, 155 g of sodium carbonate, 7.5 g of surfactant octadecyl dimethyl ammonium bromide, and 195 g of deionized water, add them to a reaction vessel, stir and react at 48° C. for 19 h to obtain solution A.

[0132] (2) Solution A was filtered, washed, and dried in a vacuum drying oven at 75° C. for 4 h to obtain VOC improved filler M5.

[0133] Preparation Example 10

[0134] (1) Weigh 95 g of 2-ethylacrylic acid and 365 g of wollastonite into a high-speed mixer and stir at 39° C. for 3 h to obtain a mixture.

[0135] (2) The mixture was cooled to room temperature and passed through an 800-mesh sieve to obtain modified wollastonite N5.

[0136] Example 5

[0137] (1) Weigh 105 parts of PS, 11.5 parts of VOC improved filler M5, 8.5 parts of modified wollastonite N5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0138] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material P5.

[0139] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0140] Comparative Example 5

[0141] (1) Weigh 105 parts of PS, 8.5 parts of modified wollastonite N5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;

[0142] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D5.

[0143] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0144] Comparative Example 5-1

[0145] (1) Weigh 105 parts of PS, 11.5 parts of VOC improved filler M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0146] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D5-1.

[0147] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0148] The PS composite materials prepared in the above Example 5, Comparative Example 5 and Comparative Example 5-1 were made into strips by injection molding machine for testing. The test data are shown in Table 5:

[0149] Table 5

[0150]

[0151]

[0152] It can be seen from the above table that, comprehensively, the mechanical properties and VOC performance of Example 5 are better.

[0153] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has good mechanical properties and VOC performance, and can expand the application field of the thermoplastic resin composite material.

[0154] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0155] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A high-strength, low-VOC thermoplastic resin composite material, characterized in that: It is composed of the following components by weight:

2. The thermoplastic resin composite material according to claim 1, characterized in that: The method for preparing the VOC improved filler comprises the following steps: (1) Weigh diatomaceous earth, sodium carbonate, surfactant, and deionized water, add them to a reaction vessel, and stir and react at 40-60° C. for 16-20 hours to obtain solution A; (2) The solution A is filtered, washed, and vacuum dried to obtain a VOC improved filler.

3. The thermoplastic resin composite material according to claim 1, characterized in that The mass ratio of diatomaceous earth, sodium carbonate and surfactant is (30-40): (10-16); (0.6-0.8): (160-240).

4. The thermoplastic resin composite material according to claim 1, characterized in that: The surfactant is octadecyl dimethyl ammonium bromide.

5. The thermoplastic resin composite material according to claim 1, characterized in that: The preparation method of the modified wollastonite comprises the following steps: Put 2-ethylacrylic acid and wollastonite into a high-speed mixer, stir them thoroughly at 30-40°C, cool them to room temperature, and sieve them to obtain modified wollastonite.

6. The thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is at least one of Irganox168, Irganox1010 and Irganox1330.

7. The thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate, and polyamide 6.

8. The method for preparing a thermoplastic resin composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) weighing a thermoplastic resin, a VOC-modified filler, a modified wollastonite, and an antioxidant according to parts by weight, mixing and stirring to obtain a mixed material; (2) The mixed material is placed in an extruder for extrusion and granulation to obtain a thermoplastic resin composite material.